Engagement in Research: A Clinical Nurse Profile and Motivating Factors. Issue 3 (May 2019) - Scala, Elizabeth; Patterson, Barbara J.; Stavarski, Debra Haas; Mackay, Periwinkle
Abstract : The purposes for this interpretive descriptive study were to gain an understanding of what motivates clinical nurses to be interested and/or engaged in research, describe the motivators for these clinical nurses, and identify common characteristics of these clinical nurses. Results revealed four themes and a clinical nurse profile. Based on findings, educators should encourage clinical nurses who are motivated to participate in nursing research to ignite intrinsic passion, professional growth, and nursing credibility and improve patient outcomes.